One Size Does Not Fit All: Private-Sector Perspectives on Climate Change, Agriculture and Adaptation - Sloan, Kealy; Teague, Elizabeth; Talsma, Tiffany; Daniels, Stephanie; Bunn, Christian; Jassogne, Laurence T.P.; Lundy, Mark M. (Springer, 2019)
Smallholder farmers around the globe are facing unstable productivity due to changing climate and weather patterns. The ways in which the private sector supports these farmers to build resilience to and/or engage in efforts to mitigate climate change can have significant impact on farmer livelihoods, security of supply of smallholder crops, and the reputation of the private sector actors drawing loyalty of end consumers and investors (Campbell (2013) Feed the future learning agenda literature review: expanded markets, value chains, and increased investment. Rockville, MD: Westat. http://pdf.usaid.gov/pdf_docs/PA00JP6B.pdf. Accessed 29 March 2018). This paper assesses how private-sector actors across the supply chain manage climate smart agriculture (CSA, with an eye on how civil society can better engage companies in promoting CSA practices. Drawing on dialogue with 42 private firms working in coffee, cocoa and other commodity crops, we found that companies used a variety of climate information depending on their proximity to farm level, drivers for decision-making, and motivations for investing in climate smart practices. In order to successfully approach companies, tool/resource developers need to understand the role of climate smart agriculture within each company’s business model and sustainability strategy (Vorley et al. (2009) Business models that are inclusive of small farmers. Agro-industries for Development. Wallingford, CABI for FAO and UNIDO, p 186–222). By providing granular data to assist in risk management of specific supply chains, tailoring tools and resources to the companies’ needs, and making the business case for CSA investment, those promoting CSA practices can better engage the private sector to invest in climate resilience.